시판 유제품을 이용한 자숙 게육의 이취 저감화 - 정효연(Hyo Yeon Jung); 김정선(Jung Sun Kim); 노봉수(Bong Soo Noh) (한국식품과학회지, 2015)
The objective of this study was to determine the effect of soaking in dairy products on the reduction of fishy odor in steamed crab meat using a mass spectrometer-based electronic nose. The steamed crab meat was soaked in three different dairy products (whole milk, soymilk, and yogurt) and the changes in the pattern of volatile components were analyzed by discriminant function analysis. The discriminant function first score (DF1) moved significantly from a negative position to a positive direction with an increase in soaking time. This suggested that the intensity of the fishy odor became weaker as soaking time increased. The effect of whole milk on the reduction of fishy odor was better than that of yogurt. The results of this study demonstrate that off-flavors can be reduced using dairy products. 자숙 게살을 우유, 두유, 요구르트, 카세인에 침지하여 유제품의 이취 제거효과를 전자코를 이용하여 비교 분석해보았다. 우유와 자숙 게살의 반응시간이 길어질수록 이취저감 효과가 나타나는 것을 알 수 있었고 두유, 요구르트와의 반응에서 또한 비슷한 경향으로 나타났다. 우유, 두유, 요구르트의 효과를 비교하기 위하여 2차원 막대그래프로 표현하여 나타내었을 때 요구르트에 비해 우유와 두유에서 이취 저감화 효과가 큰 것으로 나타났다. 또한 유제품의 주요 단백질 성분인 카세인과 반응에서 비슷한 경향을 나타내었다. 이는 자숙 게살의 이취 성분이 유제품의 단백질과 결합하여 이취제거 효과가 나타났을 것으로 예상된다. 이를 토대로 일반가정에서 활용되고 있는 우유에 생선 및 게살을 재워 비린내를 제거하는 방법의 효과를 과학적으로 입증할 수 있을 것으로 여겨지며 가정에서 손쉽게 유제품을 활용하여 이취저감화가 가능할 것이고 자숙게살의 품질관리 및 조리에 활용될 수 있을 것이다.